2014
DOI: 10.1021/sc500140x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of ZnO Nanoparticles Can Be Tailored by Modifying Their Surface Structure: A Green Chemistry Approach for Safer Nanomaterials

Abstract: ZnO nanoparticles (NP) are extensively used in numerous nanotechnology applications; however, they also happen to be one of the most toxic nanomaterials. This raises significant environmental and health concerns and calls for the need to develop new synthetic approaches to produce safer ZnO NP, while preserving their attractive optical, electronic, and structural properties. In this work, we demonstrate that the cytotoxicity of ZnO NP can be tailored by modifying their surface-bound chemical groups, while main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 35 publications
2
93
0
3
Order By: Relevance
“…At least one study has shown varied toxicology from ZnO nanoparticles depending on the synthesis route used: 27 it was determined that the two methods used to produce ZnO nanoparticles 4 resulted in different surface chemical properties, which accounted for different degrees of toxicity. 27 As another example, we previously developed a method to make composites consisting of silver or palladium nanoparticles on carbon microspheres using coffee solution, i.e., a natural reducing agent. 28 While the application of these materials as catalyst`s was within the acceptable range for the reactions used, they performed at a lower level than anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…At least one study has shown varied toxicology from ZnO nanoparticles depending on the synthesis route used: 27 it was determined that the two methods used to produce ZnO nanoparticles 4 resulted in different surface chemical properties, which accounted for different degrees of toxicity. 27 As another example, we previously developed a method to make composites consisting of silver or palladium nanoparticles on carbon microspheres using coffee solution, i.e., a natural reducing agent. 28 While the application of these materials as catalyst`s was within the acceptable range for the reactions used, they performed at a lower level than anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…The author pointed out that such NPs easily penetrated into A549 cells and were toxic in dose dependent manner [91]. The effect of the surface properties on anticancer activity was very recently documented by Punnoose and co-workers using ZnO NPs [97]. In this study, green ZnO NPs showed higher toxicity to Hut-78 lymphoma T cells than chemically synthesized ones at the same dose (0.1 mM).…”
Section: Future Science Groupmentioning
confidence: 50%
“…ZnO NPs are often coated with a variety of capping agents or surface ligands with differing chemical properties to functionalize the surface and improve stability against agglomeration and dispersibility in a given medium [16]. These surface alterations have the potential to alter their toxicity as a result of differences in the release of Zn 2+ ions and ROS production compared to bare ZnO NPs [1718]. In addition, the behaviour of surface functionalized ZnO NPs may vary compared to non-functionalized (bare) ZnO NPs by altering stability and/or agglomeration, potentially altering bioavailability and toxicity to aquatic organisms [1821].…”
Section: Introductionmentioning
confidence: 99%
“…These surface alterations have the potential to alter their toxicity as a result of differences in the release of Zn 2+ ions and ROS production compared to bare ZnO NPs [1718]. In addition, the behaviour of surface functionalized ZnO NPs may vary compared to non-functionalized (bare) ZnO NPs by altering stability and/or agglomeration, potentially altering bioavailability and toxicity to aquatic organisms [1821]. While the dissolution kinetics and agglomeration state of the ZnO NPs is known to influence the toxicity of the materials, this study aimed to determine if specific intrinsic features could be used in lieu of empirical data on the material’s behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation